A multi-level framework for efficient sensitive data transmission in cloud computing - Muhasin, Haifaa Jassim (2019)
Cloud computing, as a growing field, can provide the needs of enterprises and individuals to access cloud computing resources and meet their organizational computing requirements. The popularity of cloud computing is characterized by a number of great features, such as scalability, low cost and unlimited resources. These features have encouraged many organizations and individuals to transfer their data over the cloud. However, cloud computing is constrained by security and privacy issues, particularly by factors on confidentiality, integrity, availability and privacy, apart from access control, management and internal attacks. These issues have become a major challenge in using the cloud, especially when dealing with sensitive data. The aim of this study is to address the problem of protection in terms of privacy and security of data from the perspective of management of information systems (MIS) and its decision-making process. Here, the factors related to the management and protection of sensitive data in cloud computing are data confidentiality (DC), data integrity (DI), data privacy (DP) and data availability (DA). The analyses of these factors are performed on the basis of the interests of managers and individuals whose aim is to protect sensitive data over the cloud. The experimental study in this research includes a pilot study, the development of a tool as a proof of concept and an experts’ interview. The tool, which is developed on the basis of the proposed framework, is verified by the interviewed experts and through tool execution. The results from the interviews confirm the validity and workability of the proposed framework in enhancing the decision making of MIS and managing and protecting sensitive data over the cloud. Subsequently, the anonymization method of the proposed framework is compared with the encryption approach of previous work. The research applies the anonymization technique and classifies the contents of a sensitive data file by the k-anonymity technique, which can efficiently protect sensitive data and reduce the transmission time and size of a file sent over the cloud. The digital signature of the file containing sensitive data is generated and sent together with the file to ensure DI. Private and confidential data management issues of intrusion and data loss over the cloud are solved by using the proposed multi-level framework, which applies the method of responsible participation to maintain DC and DA upon request—the other major contribution of this research. This study has achieved its stated objectives. The results obtained by the experimental study are aligned with the proposed framework and the concept of protection and management of private confidential data for effective information management decision making.